2020
DOI: 10.1021/acs.jctc.9b00992
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Free Energy Surfaces Across a Membrane Channel Using Metadynamics and Umbrella Sampling

Abstract: To reach their site of action, it is essential for antibiotic molecules to cross the bacterial outer membrane. The progress of enhanced sampling techniques in molecular dynamics simulations enables us to understand these translocations at an atomic level. To this end, calculations of free energy surfaces for these permeation processes are of key importance. Herein, we investigate the translocation of a variety of anionic solutes through the outer membrane pore OprO of the Gram-negative bacterium Pseudomonas ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(111 citation statements)
references
References 78 publications
6
105
0
Order By: Relevance
“…This was performed via porin reconstitution into artificial bilayers and electrophysiological studies of anion transport. All experiments performed in presence of fosmidomycin demonstrate a decrease of chloride flux in dependence of fosmidomycin concentration (see Figures 2–4) which suggest, together with the published MD simulations (Golla et al., 2020), that the antibiotic can bind inside and permeate through OprO and OprP in the outer membrane of P. aeruginosa . Fosmidomycin showed already promising results in the treatment of bacterial and plasmodium infections (Lienau et al., 2019; Mine et al., 1980; Quinn et al, 2016).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This was performed via porin reconstitution into artificial bilayers and electrophysiological studies of anion transport. All experiments performed in presence of fosmidomycin demonstrate a decrease of chloride flux in dependence of fosmidomycin concentration (see Figures 2–4) which suggest, together with the published MD simulations (Golla et al., 2020), that the antibiotic can bind inside and permeate through OprO and OprP in the outer membrane of P. aeruginosa . Fosmidomycin showed already promising results in the treatment of bacterial and plasmodium infections (Lienau et al., 2019; Mine et al., 1980; Quinn et al, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…The wider constriction of OprO is definitely the reason that fosmidomycin should be able to flip better in order to permeate this pore (Golla et al. 2020). Interestingly, the concentrations for the half saturation of fosmidomycin inhibition of current through OprO, are about three orders of magnitude higher than its MIC, 17.09 μM measured in mice infections of P. aeruginosa (Mine et al., 1980).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extensive sampling in trajectories of classical MD (60 μs for the monomer and +10 μs for the homodimer) was necessary in order to generate the required large number of conformations for MSM validity [ 25 ]. Due to the large system size, extensive sampling is also important for the enhanced sampling methods to reach convergence for the associated free energy surfaces (FES) of the probed configurational space of 3CL-Pro [ 26 ]. In fact, we observed that the associated FES does not change after 8 μs of sampling at the PTmetaD-WTE level is reached.…”
Section: Methodsmentioning
confidence: 99%